Discovering and Managing Interdependence with Customer‐Entrepreneurs. (27th October 2020) - Park, Hyunkyu; Ritala, Paavo; Velu, Chander
Abstract: Research on inter‐organizational relationships has largely focused on the interdependence between formal organizations. In recent years, firms have encountered a new logic in which interdependent parties are not formal organizations but platform‐based 'customer‐entrepreneurs' that create value through illegal means. Drawing on a 5‐year‐long qualitative study, we examine how firms recognize and instantiate this new logic and, consequently, respond to their interdependencies with customer‐entrepreneurs. Viewed through the lens of institutional logic, we find that, with the benefit of hindsight, firms recognize the existence of the logic of customer entrepreneurship, which triggers organizational sensemaking that is made up of three elements: interpretation of legitimacy compatibility; interpretation of efficiency compatibility; and integration of stakeholder perspectives. This sensemaking results in either a determined account concluding on the compatibility calculus in a top‐down manner, or an open‐ended account avoiding the construction of a resolute, synthesized view. A determined account leads to a defiance strategy, by which firms attempt to remove the source of interdependencies with customer‐entrepreneurs, whereas an open‐ended account guides firms to espouse a decoupling strategy, whereby firms covertly resort to efficiency maximization enabled by the interdependence. Our results offer implications for the research on inter‐organizational relationships and institutional logic.